Postmastectomy Radiation Therapy on Permanent Implants or Tissue Expanders: Which is Better?. Issue 6 (December 2021) - Lin, Alex M.; Christensen, Joani M.; Liao, Eric C.; Cetrulo, Curtis L.; Smith, Barbara L.; Austen, William G.; Winograd, Jonathan; Colwell, Amy S.
Abstract : Objectives: This study evaluates complications and reconstructive failure rates in implant-based reconstruction with radiotherapy. Background: Postmastectomy radiotherapy may adversely affect breast reconstructive outcomes. However, the comparative effect of radiotherapy on direct-to-implant versus tissue expander-implant reconstruction has not been examined. Methods: Single institution retrospective review was performed and patients were followed 2 to 10 years. Results: Of 1566 patients, 265 patients received radiation (149 immediate implants and 116 tissue expanders). Demographics were similar except more smokers in the expander group (7.7% vs 1.3%; P = 0.012). Patients who received radiation with an expander in place had overall more complications (32.8% vs 11.4%; P < 0.001), skin necrosis (10.3% vs 4.0%; P = 0.043), wound breakdown (9.5% vs 2.7%; P = 0.029), and infections (16.4% vs 4.03%; P = 0.001) leading to a higher rate of explantation (16.4% vs 4.0%; P < 0.001). A radiation boost likewise predicted complications [odds ratio (OR) 2.199, 95% confidence interval (CI) 1.154–4.188, P = 0.017]. When comparing reconstructive outcomes, radiated expanders had a higher failure rate (21.6% vs 11.4%; P = 0.025). Revision for capsular contracture was similar between the 2 cohorts (11.4% vs 11.2%; P = 0.959) as were revision rates for contour asymmetry and breast asymmetry. In our multivariable logistic regression analysis, radiation to the expander had a higher risk of reconstruction failure than radiation to the permanent implant (OR 2.020, 95% CI 1.010–4.037, P = 0.047). Conclusion: Most patients had successful implant-based reconstructions after mastectomy and radiotherapy. Our study showed radiotherapy after direct-to-implant breast reconstruction had a lower rate of complications and reconstructive failure compared to tissue expander-implant reconstruction.